KNOWLEDGE ENCYCLOPEDIA - SARAH, LASTER (Editor) (Penguin Random House, 2017)
Incredibly detailed cross-sections and cutaways reveal the inner workings of everything - from galaxies and stars to Earth and the human body. Look inside an Apollo spacecraft, a volcano, or the body of a Tyrannosaurus Rex. Find out what happened after the Big Bang, how trench warfare worked, and the science behind a fireworks display. This fully updated edition of Knowledge Encyclopedia is the perfect reference book for inquisitive minds of all ages, covering space, Earth, nature, human body, science, and history. Packed with fascinating statistics, maps, timelines, graphics, and superb photorealistic cross-sections, this family encyclopedia makes the most complex subjects easy to understand.
Keywords: Encyclopedia; Encyclopedia - Children; Earth; Science; Space